Low cost pressure sensor for wave applications - Tan, Dominic Soon Kiat (2016)
In the recent years, the shipping industry have increased tremendously. Sea routes are getting more crowded with large cargo ships and ports get busier to handle the shipping line. Thus bigger and more powerful ships like cargo ships are built each year in order to accommodate the growing demand of this logistic supply chain. However in the environmental point of view, bigger ships means bigger ship wakes that can be harmful to the environment. As a ship powers itself through the sea, it produces large surface waves. This surface wave energy are then dissipated into the water, affecting the existing water current and surface wave. In term of land erosion by waves, this unnatural force can bring up the fine sands/sediments from the seabed. These fine sands that were picked up by this force, can travel into the mangroves area and covering them with sands and cause mangrove deforestation. Large ship wakes that occur near shore, often have waves that reaches the shoreline and hitting the shoreline. Over time, such forces cause severe land erosion by such harmful waves. Currently environmentalist and marine biologist measures the wave parameters that are caused by the ship wake, by deploying expensive wave measurement devices to forecast the impact of ship wake. Due to the high price, often a single instrument is deployed to serve are a precise measurement device over a large measurement area. However to engineers (for example hydrologist) who are required to provide a 3D wave model over a certain area, are not able to provide an accurate model due to the low spatial resolution. Hence wave detection by low cost pressure sensing are selected in this report. By trading the point accuracy of wave measurement, one can achieve higher spatial resolution by deploying more low cost pressure sensors which are often 20 times cheaper than the conventional method of using ADCPs. In this report, discussed the development of a low-cost pressure logging sensor. Two experiment have been conducted, a controlled ship wake measurement campaign and a wave directional measurement. Gravity compensation and pressure response factor are implemented into the raw pressure data, converting into useful water depth data. From the result of these two experiment, wave power/direction and wave parameters are made achievable from pressure measurement.